2000
DOI: 10.1557/proc-663-43
|View full text |Cite
|
Sign up to set email alerts
|

Study of BiPbO2NO3 for I-129 Fixation under Reducing Conditions

Abstract: Leaching of the iodide ion from BiPbO2I (BPI), BPI encapsulated in cement (BPIC) and AgI was studied in a low salinity solution and in a high salinity solution under reducing conditions. Although BPI released a limited amount of iodide ions (less than 1%) into the low salinity solution, it released more than 30% of iodide ions into the high salinity solution within 80 days. AgI released more than 30% of iodide ions into both low and high salinity solutions within 80 days. It was proved that BPI is more stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Sorbent materials containing Ag + , Cu + , Bi 3+ , Hg 2+ have been widely used to remove iodide from water by forming low solubility precipitate. One type of materials subjected to wide investigation is the sliver-containing sorbent. Ag + -containing compounds (e.g., Ag 2 O and AgCl) have been used to remove iodide from water by forming AgI precipitate. ,, In their study to extract iodide from water using Ag(0)-impregnated active carbon, Hoskins and co-workers hypothesized that Ag was first catalyzed by carbon producing Ag 2 O in the presence of dissolved oxygen, followed by sequestration of iodide in the form AgI . Using nanosilver impregnated mesoporous MCM-41, Karkhanei et al achieved a maximum adsorption capacity of 238.1 mg/g for iodide removal at pH 2 …”
Section: Introductionmentioning
confidence: 99%
“…Sorbent materials containing Ag + , Cu + , Bi 3+ , Hg 2+ have been widely used to remove iodide from water by forming low solubility precipitate. One type of materials subjected to wide investigation is the sliver-containing sorbent. Ag + -containing compounds (e.g., Ag 2 O and AgCl) have been used to remove iodide from water by forming AgI precipitate. ,, In their study to extract iodide from water using Ag(0)-impregnated active carbon, Hoskins and co-workers hypothesized that Ag was first catalyzed by carbon producing Ag 2 O in the presence of dissolved oxygen, followed by sequestration of iodide in the form AgI . Using nanosilver impregnated mesoporous MCM-41, Karkhanei et al achieved a maximum adsorption capacity of 238.1 mg/g for iodide removal at pH 2 …”
Section: Introductionmentioning
confidence: 99%
“…Another nitrate incorporated bismuth oxide, BiPbO 2 NO 3 (BPN), was developed to remove iodide ions in a solution and fix them in the solidified material BiPbO 2 I (BPI) by the ion exchange reaction (Amaya et al, 2000). An anion exchange capacity of 1.0 mEq/g and a distribution coefficient of larger than 0.1 m 3 /kg were obtained in solution at pH between 9 and 13.…”
Section: Methodsmentioning
confidence: 99%
“…Iodine can rapidly undergo exchange and be incorporated into BiPbO 2 NO 3 materials as a means of I – capture. Amaya et al demonstrated that I – is readily exchanged with NO 3 – in BiPbO 2 NO 3 to produce BiPbO 2 I and investigated the subsequent immobilization of this material in a cement matrix . In low-salinity solutions, only 1% of the iodine was released, but in high-salinity solutions, ∼30% of the iodine was released, suggesting that BiPbO 2 I may be susceptible to ionic substitution.…”
Section: Bismuth-based Materials For Contaminant Remediationmentioning
confidence: 99%